2014
DOI: 10.1002/ca.22438
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric corticospinal excitability and representation of vastus lateralis muscle in right‐handed healthy subjects

Abstract: The purpose of this study was to determine the size and location of the representations of the anterior thigh muscles on the human motor cortex in the dominant and non-dominant hemispheres. Motor-evoked potentials (MEPs) induced by transcranial magnetic stimulation were recorded from the right and left vastus lateralis (rVL, lVL) muscles. A total of ten right-handed healthy volunteers participated in the study. In a single session experiment, we investigated VL muscle corticospinal excitability (motor threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Similar to findings in upper limb, corticospinal plasticity associated with LE rehabilitation may be accompanied by changes in the size or location of motor maps. Recent LE TMS mapping studies showed symmetrical maps between left and right hemispheres for the vastus lateralis (Al Sawah et al, 2014) and rectus femoris muscles (Ward et al, 2016) in able-bodied individuals. Another LE mapping study showed a more dispersed pattern of tiblialis anterior hotspot locations in individuals post-stroke compared to healthy individuals (Sivaramakrishnan, Tahara-Eckl, & Madhavan, 2016).…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to findings in upper limb, corticospinal plasticity associated with LE rehabilitation may be accompanied by changes in the size or location of motor maps. Recent LE TMS mapping studies showed symmetrical maps between left and right hemispheres for the vastus lateralis (Al Sawah et al, 2014) and rectus femoris muscles (Ward et al, 2016) in able-bodied individuals. Another LE mapping study showed a more dispersed pattern of tiblialis anterior hotspot locations in individuals post-stroke compared to healthy individuals (Sivaramakrishnan, Tahara-Eckl, & Madhavan, 2016).…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
“…Furthermore, monosynaptic excitatory cortical projections, presumably common in upper limb muscles, may be fewer or weaker (have reduced synaptic strength) in LE muscles, such as the soleus (Bawa, Chalmers, Stewart, & Eisen, 2002; Brouwer & Ashby, 1990, 1992; Geertsen, Zuur, & Nielsen, 2010). Lower limb TMS studies have largely focused on the tibialis anterior (Beaulieu, Masse-Alarie, Ribot-Ciscar, & Schneider, 2017; Jayaram et al, 2012; Jayaram & Stinear, 2009; Sivaramakrishnan et al, 2016; Smith et al, 2017; Stinear & Hornby, 2005) and knee extensor muscles (Al Sawah et al, 2014; O’Leary, Morris, Collett, & Howells, 2015; Ward et al, 2016); with a few studies on the abductor hallucis muscle (Yen, Wang, Liao, Huang, & Yang, 2008). Variability in the strength of corticospinal connections across different lower limb muscles can markedly affect TMS-induced responses, and merits more systematic study.…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
“…A custom-designed, form-fitting cap (EasyCap GmbH, Herrsching, Germany) with stimulus sites marked at 1-cm spacing in latitude and longitude was fitted to each participant's head. [27][28][29][30] The interaural and nasion-inion distances were measured for each participant, and the vertex was aligned with the center of the cap coordinates. 31 The belly of the rectus femoris was identified through palpation during manually resisted knee extension.…”
Section: Quadriceps Corticomotor Excitability and Inhibitionmentioning
confidence: 99%
“…Investigating the feasibility of eliciting motor evoked potentials (MEPs) from different muscle groups, the anatomical constitutions need to be considered firstly. The area of the anatomic hand motor-hotspot can easily be recognized due to its omega-like shape 7 , 8 , whereas the anatomic leg motor-hotspot is located in the parasagittal cortical zone 7 , 9 12 . Previous studies found strong evidence for a very high correlation of nTMS data concerning the location of motor eloquent areas compared to intraoperative mapping so that we can assume a very high positive predictive value concerning the spatial location of nTMS positive sites 13 15 .…”
Section: Introductionmentioning
confidence: 99%